Особливості викладання теми "Методи глобальної оптимізації" для здобувачів наукового ступеня PhD групи спеціальностей "Технічні науки" - Білоусова, Тетяна Петрівна; Савчук, Володимир Петрович; Тулученко, Галина Яківна (Izdevnieciba "Baltija Publishing", 2021)
У роботі розглянуті методичні аспекти викладання теми «Методи глобальної оптимізації» для здобувачів наукового ступеня PhD групи спеціальностей «Технічні науки». The paper considers methodological aspects of teaching the topic "Global Optimization Methods" for PhD degree applicants in the "Technical Sciences" specialty group.
Features ofstudying the topic "Global optimization methods" for graduate students of the specialty "Technical engineering"
Keywords: методи оптимізації; методика викладання; optimization methods; teaching methodology